DEVELOPMENT OF ANDROID MOBILE LEARNING USING APP INVENTOR TO TRAIN HIGH SCHOOL STUDENT’S SCIENCE PROCESS SKILL - ULA IRMA, ZAHROTUL (Inovasi Pendidikan Fisika, 2017)
The purpose of research is to develope android mobile learning using app inventor to train high school studentss science process skill which feasible (valid, practical, and effective). The type of research is development research of ADDIE’s model (Analysis, Design, Development, Implementation, and Evaluation). The subject of research are 20 students of XI grade SMA Muhammadiyah 9 Surabaya. The technique of data collection are questionnaire and observation. Mobile learning is declared feasible if percentage of validity (learning, material, media), practicality (learning’s implementation is 93% with the constraint that faced was sometimes application stopped suddenly),  and effectiveness (students’s science process skills and responses) are ≥ 61% with good and excellent category. The result of research shows the validity of mobile learning is excellent (learning 93%, material 96%, and media 86%), the practicality is excellent (learning’s implementation 93%) and the constraint that faced is sometimes application stopped suddenly, and effectiveness is good (observing 100%, formulating hypotheses 65%, identifying variables 100%, interpreting data 65%, communicating 65% and students’s response are positive with percentage between 81% and 91%. Research conclude that android mobile learning using app inventor can train high school students’s science process skill. Keywords: mobile learning, android, and science process skills.